Exploration Of Risk Mitigation Practices For Problematic Financing In Bank Wakaf Mikro’s - Jaya, Tiara Juliana; Kurniawati Meylianingrum,; Kholilah, (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2022)
Financial technology; The objective of this study is to determine the development of Shariah fintech in Indonesia Maqashid al-shariah from its emergence to the present, to determine the role of Shariah fintech in the perspective of maqashid al-shariah, and to determine obstacles in the development of Shariah fintech. The research method used in this study is descriptive analysis method with a qualitative approach. The researcher performed a literature study to collect data from various sources that support the researcher’s chosen topic, i.e., all sharia fintech registered with OJK and licensed as of December 2020 associated with maqashid al-shariah. In general, Shariah fintech has fulfilled the principles of maqashid al-shariah. However, there are elements that need to be more strengthened. An example is the need for a governing regulation that separates Shariah fintech from conventional fintech regulation. This is because there are very different crucial elements and principles between these two types of fintech. As a suggestion for the development of Shariah fintech in the future, in addition to strengthening in terms of regulations, intense education related to Shariah fintech products is still needed to the wider community, especially to people who have great potential to become consumers but are not well-educated of new technologyes.